Modelling multi-modal sound transmission from point sources in ducts with flow using a wave-based method - Bennett, Gareth (My University, 2009)
An understanding of the multi-modal propagation of acoustic waves in ducts is of practical interest for use in the control of noise in, for example, aero-engines, automotive exhaust and ventilation systems. In this paper, the propagation of sound from point sources in hard-walled ducts is modelled using a numerical wave-based approach, referred to as the wave expansion method. This is a highly efficient full-domain discretisation method, which requires as few as two-to-three mesh points per wavelength. An inhomogeneous potential flow may be easily included in the method. The numerical solution for point sources embedded in the wall of a circular duct with non-reflective end-conditions and a uniform axial flow is compared with an analytical Green?s function solution. A modal decomposition technique is used to provide detailed information about the modal content of the sound field. This study provides an insightful comparison between an analytical and numerical solution to the acoustic field in a duct. The accuracy and robustness of the wave expansion method is assessed for this benchmark problem before its versatility is demonstrated with examples.
16th International Congress on Sound and Vibration (ICSV16)
PUBLISHED
Krak?w, Poland
Keywords: Mechanical & Manufacturing Engineering; Smart & Sustainable Planet